Alat Pengering Kerupuk Palembang Dengan Menggunakan Gas LPG - Ridho Pratama Fajri; Maimuzar Maimuzar; Ruzita Sumiati (Jurnal Teknik Mesin, 2017)
This cracker dryer is made considering that there are still many cracker industries that use solar thermal energy directly to dry raw crackers before the frying process, so that the cracker production results will decrease due to inefficient drying process, therefore all obstacles are always experienced when using energy sunlight can be overcome by using a cracker dryer using gas (LPG). This cracker dryer has dimensions of length 550 mm x width of 450 mm x height of 1000 mm and size of drying rack with a length of 500 mm x width of 400 mm x height of 25 mm. This tool has 4 drying racks with a capacity of each rack 1.5 kg. This dryer uses the principle of convection that is utilizing heat energy generated from the heat of the fire produced through a gas-using stove (LPG), the radiated fire produces heat that enters the drying cabinet. Hot air is locked in a drying room, so that the heat can help the drying process of crackers